Gene Expression Profile of Human Cytokines in Response to Burkholderia pseudomallei Infection - Krishnananthasivam, Shivankari (mSphere, 2017)
Melioidosis is an underreported infectious disease, caused by the Gram-negative bacterium Burkholderia pseudomallei. Understanding the disease susceptibility and pathogenesis is crucial for developing newer diagnostic and therapeutic strategies for this life-threatening infection. In this study, we aimed to analyze the gene expression levels of important cytokines in melioidosis patients and establish useful correlates with disease biomarkers compared to cases of sepsis infection caused by other pathogens and healthy individuals. A Qiagen common human cytokines array profiling the gene expression of 84 important cytokines by real-time quantitative PCR (RT-qPCR) was used. We analyzed 26 melioidosis cases, 5 healthy controls, and 10 cases of sepsis infection caused by other pathogens. Our results showed consistently upregulated expression of interleukins (IL) interleukin-4 (IL-4), interleukin-17 alpha (IL-17A), IL-23A, and IL-24, interferons (IFN) interferon alpha 1 (IFNA1) and interferon beta 1 (IFNB1), tumor necrosis factor (TNF) superfamily 4 (TNFSF4), transforming growth factor (TGF) superfamily, bone morphogenetic proteins 3 and 6 (BMP3 and BMP6), transforming growth factor beta 1 (TGFB1), and other growth factors, including macrophage colony-stimulating factor (M-CSF), C-fos-induced growth factor (FIGF), and platelet-derived growth factor alpha (PDGFA) polypeptide, in melioidosis patients compared to their expression in other sepsis cases, irrespective of comorbidities, duration of fever/clinical symptoms, and antibiotic treatment. Our findings indicate a dominant Th2- and Th17-type-cytokine response, suggesting that their dysregulation at initial stages of infection may play an important role in disease pathogenesis. IL-1A, interleukin-1 beta (IL-1B), and IL-8 were significantly downregulated in septicemic melioidosis patients compared to their expression in other sepsis cases. These differentially expressed genes may serve as biomarkers for melioidosis diagnosis and targets for therapeutic intervention and may help us understand immune response mechanisms. IMPORTANCE Melioidosis is a life-threatening infectious disease caused by a soil-associated Gram-negative bacterium, B. pseudomallei. Melioidosis is endemic in Southeast Asia and northern Australia; however, the global distribution of B. pseudomallei and the disease burden of melioidosisis are still poorly understood. Melioidosis is difficult to treat, as B. pseudomallei is intrinsically resistant to many antibiotics and requires a long course of antibiotic treatment. The mortality rates remain high in areas of endemicity, with reoccurrence being common. Therefore, it is imperative to diagnose the disease at an early stage and provide vital clinical care to reduce the mortality rate. With limitations in treatment and lack of a vaccine, it is crucial to study the immune response mechanisms to this infection to get a better understanding of disease susceptibility and pathogenesis. Therefore, this study aimed to analyze the gene expression levels of important cytokines to establish useful correlations for diagnostic and therapeutic purposes.